Children's Play in the Limelight of Contemporary Psychological Concepts. Reflections after Reading the Textbook about Play - I.V. Vachkov; S.N. Vachkova (Культурно-историческая психология)
The article is devoted to consideration and analysis of the new textbook "Early and Preschool Child Play", published in 2024. The authors strove to carry out such an analysis not simply in the framework of a review, but to consider the content of the textbook through the prism of contemporary views of psychologists on children' play in early and preschool age, taking account of classical and non-classical (in the terminology of V.T. Kudryavtsev) theories, primarily from the position of cultural-historical psychology. Thus, the main goal of the theoretical study was to analyze the content of the textbook "Early and Preschool Child Play", identifying the positions of the authors on the key issues of the phenomenon under consideration in the context of current scientific ideas about play in early and preschool ages. The analysis conducted showed the presence of substantial differences between the authors in understanding and interpreting some aspects of children's play, which once more indicates the phenomenon complexity under study and its insufficient development of not only the external manifestations of children's play activity, but also the internal processes that generate this activity, both in theoretical and empirical aspects. At the same time, according to the authors of the article, the publication of the textbook "Early and Preschool Child Play" is undoubtedly a significant and essential step in psychological and pedagogical science to embrace both the well-studied aspects of children's play and still unresolved problems of this phenomenon.